Long-term effect of in-situ soil moisture conservation (SMC) measures on soil properties in Emblica officinalis based agroforestry system - PRASAD, RAJENDRA; SHUKLA, ASHOK; SAROJ, N. K.; TRIPATHI, V. D.; KUMAR, DHIRAJ (Journal of Soil and Water Conservation, 2019)
Study was conducted to assess changes in soil’s physical, chemical and biological attributes brought by a well established 16 years old aonla (Emblica officinalis Gaertn.) or Indian gooseberry based agroforestry system subjected to different soil moisture conservation (SMC) measures (control, stone mulch, deep basin and deep basin + deep ploughing) in Bundelkhand. Representative soil samples from two sampling locations (tree-rhizosphere and non-rhizosphere zones) were drawn and analysed in laboratory for 14 soil properties viz., bulk density, water holding capacity, porosity, infiltration rate, pH, electrical conductivity, soil organic carbon, cation exchange capacity, available nitrogen (N), available phosphorus (P), available potassium (K), microbial biomass carbon, potential nitrogen mineralization and dehydrogenase activity. Significant improvements in water holding capacity, porosity, organic carbon content, cation exchange capacity, available N, available K, microbial biomass carbon, potential nitrogen mineralization and dehydrogenase activity of the soil were brought by the SMC measures over control. These effects were more pronounced in the samples collected from tree-rhizosphere than those from non-rhizosphere zone. The bulk density, infiltration rate, soil pH, electrical conductivity and available N were not affected either by the SMC techniques or sampling locations. In comparison to control, deep basin and deep basin + deep ploughing were more effective in bringing favourable changes in soil whereas stone mulch remained at par with control. Conclusively, besides yielding economic returns, aonla-based agroforestry system has shown the potential to restore health of degraded soil in Bundelkhand region of central India.